2008
DOI: 10.1093/jxb/ern244
|View full text |Cite
|
Sign up to set email alerts
|

An autophagy-associated Atg8 protein is involved in the responses of Arabidopsis seedlings to hormonal controls and abiotic stresses

Abstract: Eukaryotes contain a ubiquitous family of autophagy-associated Atg8 proteins. In animal cells, these proteins have multiple functions associated with growth, cancer, and degenerative diseases, but their functions in plants are still largely unknown. To search for novel functions of Atg8 in plants, the present report tested the effect of expression of a recombinant AtAtg8 protein, fused at its N-terminus to green fluorescent protein (GFP) and at its C-terminus to the haemagglutinin epitope tag, on the response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 71 publications
(115 reference statements)
2
98
0
2
Order By: Relevance
“…[33][34][35] Similarly to the yeast and metazoan systems the plant ATG8 proteins are critical components of the autophagy pathway, therefore in many studies the GFP-ATG8 fusions have been used as markers of autophagosomes in plants. [36][37][38][39][40][41] The lack of obvious phenotypes of atg mutants grown under nutrient-sufficient conditions suggested that autophagy was not essential for plants. However, more detailed studies reveal that the atg mutants senescent earlier and were hypersensitive to nitrogen starvation and carbon limitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] Similarly to the yeast and metazoan systems the plant ATG8 proteins are critical components of the autophagy pathway, therefore in many studies the GFP-ATG8 fusions have been used as markers of autophagosomes in plants. [36][37][38][39][40][41] The lack of obvious phenotypes of atg mutants grown under nutrient-sufficient conditions suggested that autophagy was not essential for plants. However, more detailed studies reveal that the atg mutants senescent earlier and were hypersensitive to nitrogen starvation and carbon limitation.…”
Section: Resultsmentioning
confidence: 99%
“…The process is controlled by pathways that interpret the status of cellular energy (AMP-dependent protein kinase) and nutrients (target of rapamycin), and by growth factors such as insulin. 9 The previously considered candidates for regulators of ATG genes in plants include hormones such as cytokinins 37 and ABA. 68 The physiological role of autophagy in plants grown under starvation has been studied before and it has been reported that autophagy-defective mutants are impaired in autophagosome formation and cannot survive certain starvation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, ATG8 is involved in autophagosome formation. In plants the fluorescence of GFP-AtATG8 family proteins has been assigned to what were correctly called "autophagic bodies" 16 or less carefully "autophagosome-resembling structures," 15,17 or even erroneously "autophagosomes." [18][19][20] Implication of the presence of autophagosomes is incorrect as we do not yet know the various functions of the plant ATG8 proteins.…”
Section: Methods For Visualizing Plant Autophagymentioning
confidence: 99%
“…The ability of autophagy to scavenge oxidized proteins and regulate the ROS levels suggests that autophagy may also be involved in salt and drought stresses. Some ATG genes, such as AtATG8 in Arabidopsis and OsATG10b in rice, reportedly function in response to salt stress and osmotic stress (Slavikova et al, 2008). The more direct and sufficient proof comes from the research by Bassham et al who found that high salt and osmotic stresses activate autophagy, concomitant with the upregulation of AtATG18a expression.…”
Section: Role Of Autophagy In Nutrition Starvationmentioning
confidence: 99%